Respuesta :

hey user


the answer to this is going to be


hope it helped 

if u need more help plz let me know


thanks have a good day boi

see u 

if u need more help plz let me know 

thanks 

-im out
Ver imagen heyneighbor
For this case we have the following function:
 x ^ 3-9x ^ 2 + 23x-15 = 0
 Rewriting we have:
 (x-5) * (x-3) * (x-1) = 0
 Therefore, the solutions are given by:
 Solution 1:
 x-5 = 0
 x = 5
 Solution 2:
 x-3 = 0
 x = 3
 Solution 3:
 x-1 = 0
 x = 1
 Answer:
 
x = 5
 
x = 3
 
x = 1